Theory of Planned Behavior: Analysis of Determinants of Interest Donating Alfamart Consumers in Parepare City - Pangestu, Dian Resky (Al-Sharf: Jurnal Ekonomi Islam, 2025)
Alfamart convenience store is one of the shopping places where at the end of the payment transaction, the cashier offers consumers to donate their change. This study aims to analyze the influence of Theory of Planned Behavior on consumer interest in donating. This research uses a survey method with a quantitative approach. The population is the people of Parepare City, and the sampling technique uses purposive sampling with a sample size of 100 people. Data collection was carried out through a questionnaire that had been tested for validity and reliability. The data analysis technique used was multiple linear regression. The results showed that: (1) Attitude has a positive and significant effect on consumer interest in donating with their change, with a significance value of 0.036 0.05. (2) Subjective norms do not have a significant influence on consumer interest in donating through change, with a significance value of 0.813 0.05. (3) Perceived behavioral control has a positive and significant effect on consumer interest in donating through change, with a significance value of 0.0000.05.